Ramming dry material for copper smelting system and preparation method of ramming dry material
By preparing the copper smelting system, the particles and fine powder are modified to form a dense structure, which solves the problems of easy shedding, cracking and insufficient thermal shock resistance of the copper furnace lining, and significantly improves the physical characteristics of the material and service life.
Patent Information
- Application Number
- CN202411872014.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-14
AI Technical Summary
The amorphous refractory lining of existing copper furnaces is easily affected by the pouring or ramming process, resulting in the lining falling off, cracking or passing through the furnace, and lacks thermal shock resistance and service life.
By preparing a copper smelting system, the composition includes a granule mixture, a fine powder mixture, a bonding agent, an activator, a sintering agent and a reinforcement agent, the dense structure is formed by modifying the particles and fine powder, and the dense structure is improved. The density and hardness of the material.
The compressive strength, thermal shock resistance and creep resistance of the rammed dry material is greatly improved, the service life is extended, the large liner construction operation error can tolerate, and the impact of construction on material performance is reduced.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a ramming dry material for a copper smelting system and a preparation method thereof. Background Art
[0002] A copper smelting furnace is a device used for smelting copper. It uses the reaction of molten copper ore and air to produce copper. Since the temperature of a copper smelting furnace is generally around 1200°C, high-temperature resistant materials are required as the furnace lining.
[0003] At present, the amorphous refractory lining of the copper melting furnace is greatly affected by the casting or ramming process. The existing casting or ramming technologies are uneven, and it is easy to cause improper casting or ramming, such as too thick, too thin, uneven materials, uneven thickness, loose fillers, bubbles, etc., which will cause the lining to easily fall off, crack or penetrate the furnace. In addition, if the casting or ramming is uneven, the thermal shock resistance of the furnace lining will be reduced and the service life will be short. Therefore, the development and improvement of materials need to be continuously improved in view of the fact that amorphous refractory materials are easily affected by the lining operation, which reduces the performance and service life. Summary of the invention
[0004] The first purpose of the present invention is to provide a ramming dry material for a copper smelting system, and the second purpose is to provide a method for preparing the ramming dry material for a copper smelting system.
[0005] The first object of the present invention is achieved by the following technical scheme: calculated by total weight percentage, the following components are included: 54% to 57% of a particle mixture, 33% to 35% of a fine powder mixture, 2% to 4% of a binder, 1% to 1.5% of an activator, 1% to 3% of a sintering agent, and 1% to 3% of a reinforcing agent.
[0006] The second purpose of the present invention is achieved by the following technical scheme: first, 39% of alumina and 17% of fused quartz are added to a mixer and mixed for 3-4 minutes, and sieved to prepare a granular mixture for use; secondly, 18%-22% of industrial alumina (γ-alumina), 13%-17% of lightly burned kaolin powder, 2%-4% of white mud, and 2%-5% of alumina micropowder are added to a mixer and mixed for 1-2 minutes, and sieved to prepare a fine powder mixture for use; finally, the granular mixture and fine powder mixture prepared above are added to a mixer and mixed for 3-4 minutes; then 1%-1.5% of an activator, 1%-3% of a sintering agent, and 2%-4% of a binder are added, and the mixing is continued until the mixture is evenly mixed to obtain a mixture, and the mixing time is not less than 5 minutes. The mixture is the rammed dry material.
[0007] The beneficial effects of the present invention are as follows: by modifying the particle mixture and the fine powder mixture, the surface defects and the surface porosity are reduced to form particles with a dense structure; after subsequent sintering, the crystal form of the particle structure changes and shrinks, thereby changing the characteristics of the particles from a substantial structural point of view, making the density higher, harder, and having a low creep rate; the physical properties of the rammed dry material after use, such as compressive strength, thermal shock resistance, creep resistance, etc., are greatly improved, the service life is extended, a larger lining construction operation error can be allowed, the influence of the construction operation is small, and the long-term use of the lining can be guaranteed. DETAILED DESCRIPTION
[0008] In order to enable those skilled in the art to better understand the technical solution of the present invention, its specific implementation method is described in detail below.
[0009] Example 1
[0010] A ramming dry material for a copper smelting system comprises the following components by total weight percentage: 54% of a granular mixture, 33% of a fine powder mixture, 2% of a binder, 1% of an activator, and 1% of a sintering agent.
[0011] The particle mixture comprises the following components by total weight percentage: 39% alumina and 17% fused quartz, wherein the Al2O3 content in the alumina is ≥85% and the SiO2 content in the fused quartz is ≥98%.
[0012] The alumina comprises, by total weight percentage, 14% of special-grade alumina with a particle size of 5-3 mm, 9% of special-grade alumina with a particle size of 3-1 mm, 10% of special-grade alumina with a particle size of 1-0 mm, and 13% of fused quartz with a particle size of 3-0 mm.
[0013] The fine powder mixture comprises, by total weight percentage, 18% industrial alumina (γ-alumina), 13% light-burned kaolin powder, 2%-4% white mud, and 2%-5% alumina micropowder; the particle size of the industrial alumina powder is ≤44μm; the Al2O3 content is ≥99%, the particle size of the light-burned kaolin powder is ≤44μm, the Al2O3 content is ≥43%, the SiO2 content is ≥52%, the white mud particle size is ≤74μm, the Al2O3 content of the alumina micropowder is ≥99%, and the particle size D50 is required to be 2.3μm±0.5.
[0014] The activator is zinc oxide powder with a particle size of ≤44 μm and a ZnO content of ≥99%.
[0015] The sintering agent is boric acid, and the H3BO3 content is ≥99.6%.
[0016] The binder is aluminum dihydrogen phosphate and solid water glass, and the ratio of the two in the binder is 1:1.
[0017] It also includes 1%-3% of a reinforcing agent, wherein the reinforcing agent is a rare earth or silicon carbide powder, or a mixture of rare earth and silicon carbide powder, and the ratio of the two in the reinforcing agent is 1:1-3; it can increase the density of mullite (on the other hand, kaolin can be doped with associated rare earth elements while sintering to mullite at high temperature, which greatly improves the sintering behavior of mullite ceramics, reduces the mullitization temperature and improves its mechanical properties, and enhances the corrosion resistance of the furnace lining).
[0018] Example 2
[0019] A ramming dry material for a copper smelting system comprises the following components by total weight percentage: 55% of a granular mixture, 34% of a fine powder mixture, 3% of a binder, 1% of an activator, and 2% of a sintering agent.
[0020] The particle mixture comprises the following components by total weight percentage: 39% alumina and 17% fused quartz, wherein the Al2O3 content in the alumina is ≥85% and the SiO2 content in the fused quartz is ≥98%.
[0021] The alumina comprises, by total weight percentage, 16% of special-grade alumina with a particle size of 5-3mm, 10% of special-grade alumina with a particle size of 3-1mm, 13% of special-grade alumina with a particle size of 1-0mm, and 13%-16% of fused quartz with a particle size of 3-0mm.
[0022] The fine powder mixture comprises, by total weight percentage, 20% industrial alumina (γ-alumina), 15% light-burned kaolin powder, 2%-4% white mud, and 2%-5% alumina micropowder; the particle size of the industrial alumina powder is ≤44μm; the Al2O3 content is ≥99%, the particle size of the light-burned kaolin powder is ≤44μm, the Al2O3 content is ≥43%, the SiO2 content is ≥52%, the white mud particle size is ≤74μm, the Al2O3 content of the alumina micropowder is ≥99%, and the particle size D50 is required to be 2.3μm±0.5.
[0023] The activator is zinc oxide powder with a particle size of ≤44 μm and a ZnO content of ≥99%.
[0024] The sintering agent is boric acid, and the H3BO3 content is ≥99.6%.
[0025] The binder is aluminum dihydrogen phosphate and solid water glass, and the ratio of the two in the binder is 1:1.
[0026] It also includes 1% to 3% of a reinforcing agent, wherein the reinforcing agent is a rare earth or silicon carbide powder, or a mixture of rare earth and silicon carbide powder, and the ratio of the two in the reinforcing agent is 1:1 to 3; it can increase the density of mullite (on the other hand, kaolin can be doped with associated rare earth elements while sintering to mullite at high temperature, which greatly improves the sintering behavior of mullite ceramics, reduces the mullitization temperature and improves its mechanical properties, and enhances the corrosion resistance of the furnace lining).
[0027] Example 3
[0028] A ramming dry material for a copper smelting system comprises the following components by total weight percentage: 57% of a granular mixture, 35% of a fine powder mixture, 4% of a binder, 1.5% of an activator, and 3% of a sintering agent.
[0029] The particle mixture comprises the following components by total weight percentage: 39% alumina and 17% fused quartz, wherein the Al2O3 content in the alumina is ≥85% and the SiO2 content in the fused quartz is ≥98%.
[0030] The alumina comprises, by total weight percentage, 14%-18% of special-grade alumina with a particle size of 5-3mm, 9%-12% of special-grade alumina with a particle size of 3-1mm, 10%-16% of special-grade alumina with a particle size of 1-0mm, and 13%-16% of fused quartz with a particle size of 3-0mm.
[0031] The fine powder mixture comprises, by total weight percentage, 22% industrial alumina (γ-alumina), 17% light-burned kaolin powder, 2%-4% white mud, and 2%-5% alumina micropowder; the particle size of the industrial alumina powder is ≤44μm; the Al2O3 content is ≥99%, the particle size of the light-burned kaolin powder is ≤44μm, the Al2O3 content is ≥43%, the SiO2 content is ≥52%, the white mud particle size is ≤74μm, the Al2O3 content of the alumina micropowder is ≥99%, and the particle size D50 is required to be 2.3μm±0.5.
[0032] The activator is zinc oxide powder with a particle size of ≤44 μm and a ZnO content of ≥99%.
[0033] The sintering agent is boric acid, and the H3BO3 content is ≥99.6%.
[0034] The binder is aluminum dihydrogen phosphate and solid water glass, and the ratio of the two in the binder is 1:1.
[0035] It also includes 1% to 3% of a reinforcing agent, wherein the reinforcing agent is a rare earth or silicon carbide powder, or a mixture of rare earth and silicon carbide powder, and the ratio of the two in the reinforcing agent is 1:1 to 3; it can increase the density of mullite (on the other hand, kaolin can be doped with associated rare earth elements while sintering to mullite at high temperature, which greatly improves the sintering behavior of mullite ceramics, reduces the mullitization temperature and improves its mechanical properties, and enhances the corrosion resistance of the furnace lining).
[0036] The experiment lists a method for preparing ramming dry material for copper smelting system, and the specific method is as follows: First, 39% of alumina and 17% of fused quartz were added into a mixer and milled for 3-4 minutes, and then sieved to prepare a granular mixture for use; Secondly, add 18%-22% of industrial alumina (γ-alumina), 13%-17% of light-burned kaolin powder, 2%-4% of white mud, and 2%-5% of alumina powder into a mixer and grind for 1-2 minutes, then sieve to prepare a fine powder mixture for later use; Finally, take the above-prepared granular mixture and fine powder mixture, add them into a mixer and grind them for 3 to 4 minutes; then add 1% to 1.5% activator, 1% to 3% sintering agent, 2% to 4% binder, and 1% to 3% reinforcing agent, and continue to mix and grind until the mixture is evenly mixed to obtain a mixture. The mixing time is not less than 5 minutes. The mixture is the rammed dry material.
[0037] Physical property test: Use a 160mm×40mm×40mm mold, apply a release agent to the inner wall of the mold, and use 0.1mm paper to cover the inner wall of the mold as a substitute for the release agent. Then, the rammed dry material prepared by the technical solution of this application is filled with a continuous layer-by-layer filling method to make a test strip blank of the rammed dry material; then put the rammed test strip blank and the mold into an 800℃ oven for 3 hours to make the test strip blank have a certain physical strength, take it out, cool it to room temperature, demold it, and obtain a preliminarily formed test strip blank. Secondly, adopt a step-by-step (i.e., two-stage sintering) sintering method, put the test strip blank into a sintering furnace, first sinter it at 1200℃~1250℃ for 3 hours, then increase the temperature to 1340℃~1360℃ for 3 hours, and finally take it out and cool it to obtain a high-purity, dense test strip. The test results are shown in Table 1 below.
[0038] The rammed dry material of the technical solution of the present application is used as a copper-plating furnace lining and has the characteristics of high temperature resistance, corrosion resistance, low thermal expansion coefficient, etc.
[0039] In the above process of adding and compacting the test strip blank layer by layer, each time the rammed dry material is added to the mold, each layer shall not exceed 12 mm, and it shall be compacted with a hammer, and then the surface shall be raked loose after compaction to increase the contact surface with the rammed dry material added later to avoid stratification, and then a layer of rammed dry material with a thickness of no more than 12 mm shall be added, and hammering and compaction shall continue; the above steps shall be repeated until the rammed dry material fills the mold and ensures uniform ramming. Table 1, performance test results. After the lining of the copper melting furnace is completely constructed, the temperature is raised to 1340℃~1360℃ for curing in the furnace; then the temperature is repeatedly raised and lowered at 1340℃~1360℃ to heat treat the R&D test samples, and the total high temperature of 1340℃~1360℃ is maintained for no less than 3 hours per day. The furnace is stopped after 5, 10 and 15 days of operation, and the condition of the furnace lining is observed. Area A is the bottom of the furnace lining, area B is the middle of the furnace lining, and area C is the upper part of the furnace lining. The results are shown in Table 2 below. Observation and evaluation criteria for the ramming dry material area: 0-no obvious cracks on the surface; 1-fine cracks on the surface (more than 1 and less than 10), with a maximum width of less than 1mm; 2-many fine cracks on the surface (more than 10 and less than 20), with a maximum width of less than 2mm; 3-a large number of cracks on the surface (more than 20), with a maximum width of more than 2mm, which requires timely repair.
[0040] It can be seen from the above test results that the ramming dry material of the present application can have high temperature durability, does not require maintenance during the 15-day service life, and does not have the risk of furnace penetration. It can greatly reduce the maintenance frequency, save maintenance costs, save maintenance time, and improve production efficiency.
Claims
1. A ramming dry material for a copper smelting system, characterized in that: Calculated by total weight percentage, the composition includes: 54% to 57% of a granular mixture, 33% to 35% of a fine powder mixture, 2% to 4% of a binder, 1% to 1.5% of an activator, and 1% to 3% of a sintering agent.
2. The ramming dry material for copper smelting system according to claim 1, characterized in that: The particle mixture comprises the following components by total weight percentage: 39% alumina and 17% fused quartz, wherein the Al2O3 content in the alumina is ≥85% and the SiO2 content in the fused quartz is ≥98%.
3. The ramming dry material for copper smelting system according to claim 2, characterized in that: The alumina comprises, by total weight percentage, 14%-18% of special-grade alumina with a particle size of 5-3mm, 9%-12% of special-grade alumina with a particle size of 3-1mm, 10%-16% of special-grade alumina with a particle size of 1-0mm, and 13%-16% of fused quartz with a particle size of 3-0mm.
4. The ramming dry material for copper smelting system according to claim 1, characterized in that: The fine powder mixture comprises, by total weight percentage, 18%-22% of industrial alumina (γ-alumina), 13%-17% of light-burned kaolin powder, 2%-4% of white mud, and 2%-5% of alumina micropowder; the particle size of the industrial alumina powder is ≤44μm; the Al2O3 content is ≥99%, the particle size of the light-burned kaolin powder is ≤44μm, the Al2O3 content is ≥43%, the SiO2 content is ≥52%, the white mud particle size is ≤74μm, the Al2O3 content of the alumina micropowder is ≥99%, and the particle size D50 is required to be 2.3μm±0.
5.
5. The ramming dry material for copper smelting system according to claim 1, characterized in that: The activator is zinc oxide powder with a particle size of ≤44 μm and a ZnO content of ≥99%.
6. The ramming dry material for copper smelting system according to claim 1, characterized in that: The sintering agent is boric acid, and the H3BO3 content is ≥99.6%.
7. The ramming dry material for copper smelting system according to claim 1, characterized in that: The binder is aluminum dihydrogen phosphate and solid water glass, and the ratio of the two in the binder is 1:
1.
8. The ramming dry material for copper smelting system according to claim 1, characterized in that: It also includes 1% to 3% of a reinforcing agent, wherein the reinforcing agent is rare earth or silicon carbide powder, titanium carbide, or a mixture of rare earth and silicon carbide powder, and the ratio of the two in the reinforcing agent is 1:1 to 3.
9. A method for preparing a ramming dry material for a copper smelting system according to any one of claims 1 to 8, characterized in that: First, add 39% alumina and 17% fused quartz into a mixer and mix for 3-4 minutes, sieve to prepare a granular mixture for use; secondly, add 18%-22% industrial alumina (γ-alumina), 13%-17% light-burned kaolin powder, 2%-4% white mud, and 2%-5% alumina micropowder into a mixer and mix for 1-2 minutes, sieve to prepare a fine powder mixture for use; finally, add the above-prepared granular mixture and fine powder mixture into a mixer and mix for 3-4 minutes; then add 1%-1.5% activator, 1%-3% sintering agent, 2%-4% binder, and 1%-3% reinforcing agent, continue mixing until the mixture is evenly mixed to obtain a mixture, and the mixing time is not less than 5 minutes. The mixture is the rammed dry material.
Citation Information
Patent Citations
Homogeneous material-containing corundum-mullite high-strength abrasion-resisting plastic
CN102030550A
Environment-friendly ramming material and preparation method thereof
CN107235735A
Refractory ramming mass for hot metal ladle of ferrosilicon electric furnace and preparation method for refractory ramming mass
CN110642611A